2021
DOI: 10.1155/2021/2462832
|View full text |Cite
|
Sign up to set email alerts
|

Quality of YouTube Videos on Laparoscopic Cholecystectomy for Patient Education

Abstract: Background. Surgical patients frequently seek information from digital sources, particularly before common operations such as laparoscopic cholecystectomy (LC). YouTube provides a large amount of free educational content; however, it lacks regulation or peer review. To inform patient education, we evaluated the quality of YouTube videos on LC. Methods. We searched YouTube with the phrase “laparoscopic cholecystectomy.” Two authors independently rated quality of the first 50 videos retrieved using the JAMA, Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…These scoring systems were chosen due to the numerous previous studies utilizing them to identify the quality of information presented on YouTube. 7,[12][13][14] Specific to craniofacial surgery, Korkmaz et al 15 and Bozkurt et al 16 found that YouTube was not a reliable source of information for cleft lip and palate repairs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These scoring systems were chosen due to the numerous previous studies utilizing them to identify the quality of information presented on YouTube. 7,[12][13][14] Specific to craniofacial surgery, Korkmaz et al 15 and Bozkurt et al 16 found that YouTube was not a reliable source of information for cleft lip and palate repairs.…”
Section: Introductionmentioning
confidence: 99%
“…6 This is especially relevant at the time of writing given the impact that the COVID-19 pandemic has had on patients’ ability to access more traditional, face-to-face healthcare consultations. 7 It is therefore even more important to identify quality sources for patient education, as people turn to online platforms, such as YouTube.…”
Section: Introductionmentioning
confidence: 99%
“…2). eTable 6, Supplemental Digital Content 1, http://links.lww.com/SLA/E605 denotes individual study characteristics 19–74 …”
Section: Resultsmentioning
confidence: 99%
“…To assess content quality, a score was assigned to two aspects: the comprehensive aspect and the floating agriculture element aspect. The authors developed the content grading standards for floating farm element characteristics, and comprehensive features were updated by evaluating previous research ( Hewitt et al., 2021 ). One point was awarded for meeting each metric, for a total of 22 criteria.…”
Section: Methodsmentioning
confidence: 99%